2016
DOI: 10.1002/jbmr.2782
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Domain-Specific Mutation in a Sclerosteosis Patient Suggests a Role of LRP4 as an Anchor for Sclerostin in Human Bone

Abstract: Mutations in the LRP4 gene, coding for a Wnt signaling coreceptor, have been found to cause several allelic conditions. Among these, two are characterized by a strong skeletal involvement, namely sclerosteosis and Cenani-Lenz syndrome. In this work, we evaluated the role of LRP4 in the pathophysiology of these diseases. First, we report a novel LRP4 mutation, leading to the substitution of arginine at position 1170 in glutamine, identified in a patient with sclerosteosis. This mutation is located in the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 33 publications
3
61
0
2
Order By: Relevance
“…A number of reports were exploded to highlight the role of the Wnt/β-catenin pathway in the regulation of bone homeostasis (57)(58)(59). Recently, the most highlighted members of the LDLR family involved in the maintenance of bone metabolism were LRP5, LRP6, LRP4, and Apoer2 (26,60). Interestingly, results in the current study showed that all of these four members were induced during osteoblast differentiation (Figure 1).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A number of reports were exploded to highlight the role of the Wnt/β-catenin pathway in the regulation of bone homeostasis (57)(58)(59). Recently, the most highlighted members of the LDLR family involved in the maintenance of bone metabolism were LRP5, LRP6, LRP4, and Apoer2 (26,60). Interestingly, results in the current study showed that all of these four members were induced during osteoblast differentiation (Figure 1).…”
Section: Discussionmentioning
confidence: 58%
“…ApoE has a strong affinity for and is the main ligand for members of the LDLR family. The LDLR family is a highly conserved receptor family with diverse functions in cellular physiology (shown in Table 1) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). LDLR is the prototype of the entire family, and members of this family are structurally and functionally related to it.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that Sclerostin directly interacts with several members of the BMP and Wnt pathways such as BMP4, BMP2 and Lrp 4/5/6 (4;77;95;96). More recently, using a sclerostin affinity capture technique and mass spectrometry, it was shown that alkaline phosphatase, carbonic anhydrase, gremlin-1, fetuin A, midkine, annexin A1 and A2, and collagen α1, bind to sclerostin (97).…”
Section: Sost/sclerostin Functionmentioning
confidence: 99%
“…[72][73][74] LRP4 is another member of the Wnt pathway family of proteins important in bone mass regulation. It was first identified in genome-wide studies 6,9,19 and in both mice 75,76 and humans 11,12 and shown to regulate bone mass. LRP4 functions as a binding or docking protein for sclerostin.…”
Section: Hyperostosis and Osteosclerosismentioning
confidence: 99%
“…LRP4 functions as a binding or docking protein for sclerostin. 11,12,75 Thus, while LRP4 was first identified as a candidate gene for bone mass from GWAS studies, the identification of human mutations with the rare bone disorders provided important confirmatory evidence for its role in human bone mass regulation.…”
Section: Hyperostosis and Osteosclerosismentioning
confidence: 99%